Dialógica da inovação - Rodrigues, Talissa Cristini Tavares (2021)
For an innovation capable of transforming education, it is necessary to reform thinking. In addition to centering on the pillars “learning to know; learn to do; learn to be; learn to live together”, according Delors (p.30, 2010), it is necessary to be aware about of the complexity of the world and recognize that innovate is not creating something unprecedented, but rather generating changes in a conceived system .Assuming such assumptions, this case study was dedicated to the diagnosis of possible epistemological limitations for a paradigmatic innovation in the teaching of Nature Sciences, from dimensions built based on the conceptions of teachers and future teachers, from two universities from Rio Grande do Sul. The results corroborating with state of art studies about the concept of innovation, demonstrating that the polysemic scenario of innovation is persistent. A differentiated pattern was also identified between the action of innovate and the object (innovative teaching). As we consider the meaning of the action innovate, the subjects demonstrated, although minimally, proximity with parameters of a paradigmatic education. Nevertheless, when approaching teaching in the totality, the subjects do not identify themselves as transforming agents in the innovation process. In this scenario, following ideas were identified: deep reform (change in the view of Science); Digital Culture (insertion of digital culture in school culture) and The Method (motivator for content), as opposed to Educational Reform (derived from public policies), Digital Culture (as a sign, insertion of technology in the school environment) and The Method (keep the initial meaning). It is concluded that the epistemological conception around the method, from its structures that maintain a reproductive educational vision, represents a possible epistemological obstacle for a paradigmatic innovation. Although the desire for results and performance is not abandoned, around content-based learning, the concepts of innovation demonstrate that they understand the need to know students' ideas, even if on a “small scale”, with the teacher as a mediator in the processes. It is suggested that, in this scenario, universities are dedicated to understanding the obstacle and analyzing structures that prevent paradigmatic innovation, rethinking their curriculum, their methodologies and culture of innovation in the teaching of Nature Sciences.